Care partners reading patients' visit notes via patient portals: Characteristics and perceptions. Issue 2 (February 2022) - Jackson, Sara L.; Shucard, Hannah; Liao, Joshua M.; Bell, Sigall K.; Fossa, Alan; Payne, Thomas H.; Reisch, Lisa M.; Radick, Andrea C.; DesRoches, Catherine M.; Fitzgerald, Patricia; Leveille, Suzanne; Walker, Jan; et al.
Highlights: Compared to patients, care partners perceived greater importance for patient health behaviors from access to reading patient visit notes. Care partners aged 25-64 years most strongly endorsed the importance of access to notes when choosing a future doctor. Care partners suggested separate portals for care partners, navigable websites, and non-judgmental language in visit notes. Care partners perceived greater importance for patient health behaviors, compared to patients, from access to reading patient visit notes. Abstract: Background: Care partners are key members of patients' health care teams, yet little is known about their experiences accessing patient information via electronic portals. Objective: To better understand the characteristics and perceptions of care partners who read patients' electronic visit notes. Patient involvement: Focus groups with diverse patients from a community health center provided input into survey development. Methods: We contacted patient portal users at 3 geographically distinct sites in the US via email in 2017 for an online survey including open ended questions which we qualitatively analyzed. Results: Respondents chose whether to answer as care partners (N = 874) or patients (N = 28, 782). Among care partner respondents, 44% were spouses, 43% children/other family members, and 14% friends/neighbors/other. Both care partners and patients reported that access to electronic notes was very important for promoting positive health behaviors, but care partners' perceptions of importance were consistently more positive than patients' perceptions of engagement behaviors. Open-ended comments included positive benefits such as: help with remembering the plan for care, coordinating care with other doctors, decreasing stress of care giving, improving efficiency of visits, and supporting patients from a geographical distance. They also offered suggestions for improving electronic portal and note experience for care partners such as having a separate log on for care partners; having doctors avoid judgmental language in their notes; and the ability to prompt needed medical care for patients. Discussion: Care partners value electronic access to patients' health information even more than patients. The majority of care partners were family members, whose feedback is important for improving portal design that effectively engages these care team members. Practical value: Patient care in the time of COVID-19 increasingly requires social distancing which may place additional burden on care partners supporting vulnerable patients. Access to patient notes may promote quality of care by keeping care partners informed, and care partner's input should be used to optimize portal design and electronic access to patient information.